An analytical study on enacting teen curfew law in Malaysia / Tengku Nurul Syuhada Tengku Abdul Azis … [et al.] - Tengku Abdul Azis, Tengku Nurul Syuhada; Mahamad Rappek, Nurhusna; Ibrahimi Husaimi, Nor Amirah; Abdul Mutalib, Zulaikha (Faculty of Law, 2014)
The issues of juvenile crimes and social problems have become one of the biggest issue in Malaysia. Most people only know to talk or become the "keyboard warrior" in judging the committers. However, without realized, there is still no concrete way to curb this problem. Thus, in order to deter this problem, our group consists of four members had agreed to propose the enactment of teen curfew law in Malaysia. In our country, there is no such law has been implementing, therefore we had agreed to choose United States of America as the role model. By this research, we had received goods responds from the respondents which they are agreed for the implementation of this law in our country.